2019
DOI: 10.3847/1538-4357/aafa76
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Characterization of C3H and C5H and Their Anions

Abstract: Highly correlated ab initio calculations are employed for the structural and spectroscopic characterization of small odd chains of type C 2n+1 H, considering neutral forms, cations, and giving special attention to the anions. This work confirms the stability of the linear carbon chains and carbon clusters containing three-body rings. The smallest species, C 3 H, displays three stable structures, whereas C 5 H possesses at least 8 neutral isomers and 11 and 10 isomers with a negative or a positive charge. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 65 publications
(97 reference statements)
4
13
1
Order By: Relevance
“…Two-color photodetachment studies by Tulej et al (2011) suggested that the ground state is 3 Σ − with a linear structure and a rotational constant of 2476.3 ± 6 MHz. In addition, the reported experimental value for the C 5 H − ( 3 Σ − ) species differs by more than 100 MHz from the predicted values obtained by Bennedjai et al (2019) and our scaled value (Table 2). Moreover, if that assignment were correct, C 5 H − could not be the carrier of the observed lines as significant hyperfine structure is expected due to the spin 1/2 of H and the low spin-spin interaction constant derived, λ = 7200 ± 4500 MHz.…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations
“…Two-color photodetachment studies by Tulej et al (2011) suggested that the ground state is 3 Σ − with a linear structure and a rotational constant of 2476.3 ± 6 MHz. In addition, the reported experimental value for the C 5 H − ( 3 Σ − ) species differs by more than 100 MHz from the predicted values obtained by Bennedjai et al (2019) and our scaled value (Table 2). Moreover, if that assignment were correct, C 5 H − could not be the carrier of the observed lines as significant hyperfine structure is expected due to the spin 1/2 of H and the low spin-spin interaction constant derived, λ = 7200 ± 4500 MHz.…”
Section: Resultscontrasting
confidence: 89%
“…Hence, our ab initio calculations provide conclusive arguments for the spectroscopic identification of C 5 H + using our sensitive QUIJOTE survey of TMC-1. Using the B e value calculated by Bennedjai et al (2019) for C 5 H, and correcting B e of C 5 H + by their ratio B obs (C 5 H)/B e (C 5 H), we found B 0 (C 5 H + ) ∼ 2408.3 MHz, which also agrees well with our experimental rotational constant.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…clusive arguments for the spectroscopic identification of C 5 H + using our sensitive QUIJOTE survey of TMC-1. Using the B e value calculated by Bennedjai et al (2019) for C 5 H, and correcting B e of C 5 H + by their ratio B obs (C 5 H)/B e (C 5 H), we found B 0 (C 5 H + ) ∼ 2408.3 MHz, which also agrees well with our experimental rotational constant.…”
Section: Resultssupporting
confidence: 87%